Adaptaciones curriculares para estudiantes con necesidades educativas especiales de la escuela de educación básica" Jorge Washington" en el periodo lectivo 2020-2021. - Estrada, Carolina A. (2022)
The educational system in its different support systems should promote inclusive education aimed at students with special educational needs associated or not with a disability, a population that requires permanent or temporary curricular adaptation in the teaching-learning process in order to access the national curriculum. The objective of this research was to analyze the curricular adaptations for students with Special Educational Needs at the "Jorge Washington" School of Basic Education, in the school year 2020-2021; an educational institution of fiscal support located in the Historic Center of the Quito canton, province of Pichincha - Ecuador. The approach and type of research used was qualitative descriptive with a non-experimental design. The techniques and instruments used were the survey with its respective questionnaire and the interview, which allowed obtaining direct information from the population to be investigated; 23 teachers of the educational institution, the authority of the same and 17 legal representatives of students with special educational needs participated in the research, being a small population, it was not necessary to consider a sample. The results obtained in the research were not very favorable in relation to the application of curricular adaptations for students with special educational needs of the educational institution.